ABOUT ONE PROBLEM FOR THE EQUATION OF THE THIRD ORDER WITH A NON - LOCAL CONDITION - Turgunov Azizjon Mamsliyevich,; Asqaraliyeva Muxtasarxon Azizjon qizi, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the paper nonlocal problem for equation of the third order with multiple characteristics are consider